Feeding Practices of Sick Newborns Admitted in Neonatal Ward of ICMH: Breast Milk as the Only Food - Akter, Nasima; Khatoon, Soofia; Khanom, Wahida (Bangladesh Journal of Child Health, 2012)
Background: Breast milk is uniquely adopted most appropriate natural, preferred food for all infants including premature and sick newborns. It protects babies against many diseases and infections, better intelligence and greater academic achievement, lower risk for developing recurrent wheezing than children who were infant-formula fed. Objectives: The objective of the study is to see how early breast feeding could be started and when exclusive breast feeding could be established in admitted sick newborn. Materials and methods: This was a observational prospective study through a structured questionnaire conducted in Neonatal ward of Institute of Child and Mother Health. One hundred and sixty three sick newborns admitted in neonatal ward during November, 2005 to January, 2006 with weight more than 1200 gm, gestational age more than 32 weeks without major congenital anomaly were studied. Admitted babies were kept nill by mouth or nasogastric tube feeding and/or oral feeding as clinical condition permitted. Parenteral fluid was started as recommended daily fluid and gradually was advanced to oral or nasogastric tube feeding or spoon feeding of expressed breast milk as 1 to 3 hourly feeding which was individualized. During hospital stay, mothers were encouraged and motivated to breast feed and/or to expression of breast milk. Patients discharged when full breast feeding was established. Daily weight measurement and follow up were done after 7, 15, 30 days of discharge. Results: Among 330 admitted neonates, 163 were enrolled in this study. Mean age at presentation was 2.8 days. About one third of babies 55 (33.7%) had appropriate birth weight, seventy eight (47.8%) had perinatal asphyxia, and one third 55 (33.7%) had septicemia. Mean age of 1st feed was 2.9 days. Minimal and maximal days for initiation of breast feeding were 1st and 24th - day respectively. Mean days of full feeding was 3.6 days. About 67 (41%) of babies received and tolerated 1st feeding in between 24-72 hours and 48 babies (29.5%) in between 3rd-5th day. Out of 163 patients, weight gained in 22 (13%) babies during hospital stay. Average weight gain was 10 gram/day. Ninety two (55%) of study neonates needed assisted feeding with nasogastric tube. In spite of sickness breast feeding could be started in 22 (13.5%) neonates. Full feeding was established on 1st day in 44 (27%) of study neonates and in 80 (49%) neonates full feeding was established by 10 days. Expressed breast milk was from beginning in 66 (70%) of neonate. One hundred and thirty six neonates (83.4%) came for 1st follow up, 110 (67%) came for 2nd follow up, 144 (88%) babies came for 3rd follow up. Weight gain were found in 85%, 63.8%, 82% respectively. Conclusion: We can say from the present study that breast milk either by suckling or through nasogastric tube can safely be given to sick neonates under supervision and by that baby can maintained on normal weight gain. DOI: http://dx.doi.org/10.3329/bjch.v35i1.10365 BJCH 2011; 35(1): 1-5